Hazardous atmospheres and respirators - Safetycare Australia (Australia : Safetycare Australia, 2004)
Looks at what constitutes hazardous atmospheres as well as the acute and chronic effects on health. Discusses air-purifying and supplied-air respirators, their proper use and limitations. Addresses fit tests and user seal checks. Outlines selection of appropriate filters, cartridges and canisters. Highlights signs of respirator failure and discusses inspection and maintenance
Accompanied by trainer's manual
Title from title screen
VCD format
Keywords: Hazardous substances -- Safety measures; Respirators; Industrial safety